Pengaruh Kedalaman yang Berbeda terhadap Pertumbuhan dan Kandungan Karaginan Rumput Laut Kappaphycus alvarezii - Soares, Godevilia MO; Ratoe Oedjoe, Marcelien Dj; Turupadang, Welem (Jurnal Aquatik, 2024)
One of the carrageenan-producing seaweed is Kappaphycus alvarezii which grows in the waters of NTT. The purpose of this study was to determine the carrageenan content and growth depth of K. alvarezii seaweed. From October 25, 2022 to December 15, 2022, research was conducted for 45 days in the waters of Tablolong, West Kupang Regency, East Nusa Tenggara Province. The longline approach was used to grow K. alvarezii seaweed. This method has three treatments and three replicates with treatment I 10 m apart, treatment II 20 m apart, and treatment III 30 m apart. Data on daily growth, absolute growth, carrageenan content, and water quality obtained from the results were then analyzed using ANOVA and added into graphs. The findings showed that the growth and carrageenan content of seaweeds in the sea around Tablolong Village were affected by different depths. K. alvarezii seaweed has the largest absolute growth in treatment C, which is 156 g, while treatment A has the lowest growth value, which is 135g. Treatment C also has the highest carrageenan content of 92.9%, while treatment A has the lowest carrageenan content of 67.7%. The results of this study indicate that the growth and carrageenan content of K. alvarezii seaweed is influenced by water depth. Keywords: Kappaphycuz alvarezii, carrageenan, depth and growth